Evaluation of the quality of E-payment services in Algeria - Merrad , Rais (Journal of Excellence for Economics and Management Research, 2024)
we study in this research an important topic, it is the impact of service quality’s dimensions on e-payment service, and the relationship between them. to achieve this, we distributed a survey to a sample of users. the study revealed that all components of service quality values were at a moderate level. furthermore, in our study, we used simple regression analysis, identified that only three dimensions (reliability, assurance and empathy) significantly influenced in e-payment quality. conversely, the other dimensions (tangibility and responsiveness) showed no significant impact.